Angst Geht Um
This broadcast focuses on the ethnic Hungarian minority in Vojvodina, a formerly autonomous region now controlled by Serbia. Ethnic Hungarians from the former Yugoslavia living in Budapest and Novi Sad, capital of the region, are interviewed about the war. The plight of ethnic Hungarians in Vojvodina during the conflict is explored, showing how many face conscription to fight for a Serbian-controlled JNA, as well as their relationship to Hungary proper. Andras Agostan, leader of the ethnic Hungarians in Vojvodina, and Maja Gojkovic, representative for the Serbian Radical Party in the region, speak on the present situation there.